Lumbar Fusion Surgery for Patients With Back Pain and Degenerative Disc Disease: An Observational Study From the Canadian Spine Outcomes and Research Network. Issue 8 (October 2022) - Evaniew, Nathan; Swamy, Ganesh; Jacobs, W. Bradley; Bouchard, Jacques; Cho, Roger; Manson, Neil A.; Rampersaud, Y. Raja; Paquet, Jerome; Bailey, Christopher S.; Johnson, Michael; Attabib, Najmedden; Fisher, Charles G.; et al.
Study Design: Uncontrolled retrospective observational study. Objectives: Surgery for patients with back pain and degenerative disc disease is controversial, and studies to date have yielded conflicting results. We evaluated the effects of lumbar fusion surgery for patients with this indication in the Canadian Spine Outcomes and Research Network (CSORN). Methods: We analyzed data that were prospectively collected from consecutive patients at 11 centers between 2015 and 2019. Our primary outcome was change in patient-reported back pain at 12 months of follow-up, and our secondary outcomes were satisfaction, disability, health-related quality of life, and rates of adverse events. Results: Among 84 patients, we observed a statistically significant improvement of back pain at 12 months that exceeded the threshold of Minimum Clinically Important Difference (MCID) (mean change -3.7 points, SD 2.6, p < 0.001, MCID = 1.2; 77% achieved MCID), and 81% reported being "somewhat" or "extremely" satisfied. We also observed improvements of Oswestry Disability Index (-17.3, SD 16.6), Short Form-12 Physical Component Summary (10.3, SD 9.6) and Short Form-12 Mental Component Summary (3.1, SD 8.3); all p < 0.001). The overall rate of adverse events was 19%. Conclusions: Among a highly selective group of patients undergoing lumbar fusion surgery for degenerative disc disease, most experienced a clinically significant improvement of back pain as well as significant improvements of disability and health-related quality of life, with high satisfaction at 1 year of follow-up. These findings suggest that surgery for this indication may provide some benefit, and that further research is warranted.